2012
DOI: 10.1021/jp302784r
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated H-Bonding between Porphyrins on Metal Surfaces

Abstract: Using a combination of X-ray photoelectron spectroscopy (XPS) and core level shift first principles calculations, we determine the formation of an unusual intermolecular interaction between porphyrin molecules. We show that protoporphyrin IX molecules (H2PPIX) adsorbed on Cu surfaces at low temperature (LT) form molecular adlayers stabilized by a strong (1.3 eV) tetragonal coordinated H-bond. This unconventional H-bonding involves the four nitrogen atoms in the tetrapyrrole macrocycle of one molecule, four hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 40 publications
4
24
0
Order By: Relevance
“…In fact, the hydrogen bond between OH and H 2 O (length 1.71Å) reduces the O-1s binding energy on the coordinated H 2 O molecule by 0.64 eV compared to the other water molecules. The reduction of core-level binding energies by H-bonds is a well-documented effect [22,35]. The broadening and redshift observed in Fig.…”
Section: Resultsmentioning
confidence: 68%
“…In fact, the hydrogen bond between OH and H 2 O (length 1.71Å) reduces the O-1s binding energy on the coordinated H 2 O molecule by 0.64 eV compared to the other water molecules. The reduction of core-level binding energies by H-bonds is a well-documented effect [22,35]. The broadening and redshift observed in Fig.…”
Section: Resultsmentioning
confidence: 68%
“…A complex hydrogen-bonded network consisting of 2HPPIX molecules (see Fig. 4) on various Cu and Au surface was described by Garcia-Lekue et al [507]. [380].…”
Section: Other Networkmentioning
confidence: 91%
“…[27] It has also been shown that protoporphyrin IX (PPIX, 71)a dsorbed on aC us urface at low temperature forms adlayers stabilized by tetragonal Hbonds between the nitrogen atoms of the macrocycle core and peripherally bound carboxyl groups. [28] Looking at examples in nature,t he malaria pigment hemozoin, ad isposal product from the digestion of blood by malaria parasites,i sa ni nsoluble,p eripherally hydrogen-bonded dimer of b-hematin. [29] And in chlorosomes,p hotosynthetic antenna complexes found in some anaerobic bacteria, hydrogen bonding can have ac ritical influence on exciton dynamics and as such, the light-harvesting process itself.…”
Section: Coordination Types In Porphyrins 121 Peripheral H-bondingmentioning
confidence: 99%
“…Further examples of the directing and reinforcing characteristics of hydrogen bonds are found in porphyrinic solids, self‐assembled monolayers (SAMs), nanofibers and nanorods, and nanochannels of 2,3,5,7,8,10,12,13,15,17,18,20‐dodecaphenylporphyrin (H 2 DPP, 64 ) derivatives . It has also been shown that protoporphyrin IX (PPIX, 71 ) adsorbed on a Cu surface at low temperature forms adlayers stabilized by tetragonal H‐bonds between the nitrogen atoms of the macrocycle core and peripherally bound carboxyl groups …”
Section: Introductionmentioning
confidence: 99%